Erratum: QUANHONG ZHANG, ALEXEY V. SOLOVYEV, JIAMIN LIANG, MIN WANG & HOUSHUAI WANG (2023) A new species of Griseothosea (Lepidoptera, Limacodidae) from Wuyishan National Park, China. Zootaxa, 5323 (3), 429–434. - Zhang, Quanhong; Solovyev, Alexey V.; Liang, Jiamin; Wang, Min; Wang, Houshuai (Zootaxa, 2023)
N/A